Overview of Hepatitis B Surface Antigen Examination Results in Health Analyst Study Program Students of STIKes Muhammadiyah Ciamis - Epi Amalia; Atun Farihatun; Euis Tia Istianah (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective: Hepatitis B can also be called a liver infection caused by the Hepatitis B Virus (VHB). Health workers are at high risk of being infected with the Hepatitis B Virus, this is due to a lack of knowledge and skills such as the use of Personal Protective Equipment and not implementing health protocols which can cause exposure to the Hepatitis B Virus. This study aims to determine the description of the results of the Hepatitis B surface Antigen examination in Health Analyst Study Program Students of STIKes Muhammadiyah Ciamis. Method: This study is a descriptive study with a purposive sampling technique conducted in May 2023. Respondents in this study were students of STIKes Muhammadiyah Ciamis as many as 38 respondents with measurements using the Sandwich method ELISA which then the results were processed manually and displayed in tabular format for narration. Result: The results of the Hepatitis B Surface Antigen examination showed that all respondents were 100% negative for Hepatitis B. Conclusion: The research that has been carried out, shows that all respondents, namely students of the Health Analyst Study Program at STIKes Muhammadiyah Ciamis, are not exposed to the Hepatitis B virus.